A visual analytics process for maritime response, resource allocation and risk assessment. (April 2014) - Malik, Abish; Maciejewski, Ross; Jang, Yun; Oliveros, Silvia; Yang, Yang; Maule, Ben; White, Matthew; Ebert, David S
In this paper, we present our collaborative work with the U.S. Coast Guard's Ninth District and Atlantic Area Commands, in which we develop a visual analytics system to analyze historic response operations and assess the potential risks in the maritime environment associated with the hypothetical allocation of Coast Guard resources. The system includes linked views and interactive displays that enable the analysis of trends, patterns, and anomalies among the U.S. Coast Guard search and rescue (SAR) operations and their associated sorties. Our system allows users to determine the change in risks associated with closing certain stations in terms of response time and potential lives and property lost. It also allows users to determine which stations are best suited to assuming control of the operations previously handled by the closed station. We provide maritime risk assessment tools that allow analysts to explore Coast Guard coverage for SAR operations and identify regions of high risk. The system also enables a thorough assessment of all SAR operations conducted by each Coast Guard station in the Great Lakes region. Our system demonstrates the effectiveness of visual analytics in analyzing risk within the maritime domain and is currently being used by analysts at the Coast Guard Atlantic Area.